Experimental warming of subarctic biocrust: Temporal responses of soil respiration and plant community - Eyrún Gyða Gunnlaugsdóttir 1989- (2022)
Thesis approved in partial fulfilment of a double Nordic Master MSc degree in environmental changes at higher latitudes (EnCHiL), from University of Helsinki and Agricultural University of Iceland. Biological soil crust, biocrust, is a significant contributor to biogeochemical cycles through nitrogen and carbon cycling. Further, it stabilizes soil, facilitates water infiltration, and mitigates soil erosion. The global biocrust cover is believed to decrease by about 25-40% in the next 60 years due to climate change and intensification in land use. Research on biocrust in arctic and subarctic regions is limited, much of the knowledge comes from lower latitudes in arid and semiarid ecosystems. Cold-adapted biocrust might respond differently to increasing temperatures when compared with warm-adapted biocrust. Therefore, it is fundamental to research biocrust in arctic and subarctic regions when looking at how fast the climate is changing in the Northern hemisphere. Temporal variations of soil respiration in subarctic biocrust have not been studied systematically before. This research project focuses on the effects of warming on soil respiration in biocrust, on a diurnal and a seasonal scale. It also focuses on species composition changes of vascular plants in the warming experiment where warming was induced with open-top chambers (OTCs). Soil respiration, temperature, soil water content, as well as plant species composition changes were measured during three field trips that each lasted four days during the growing season of 2021. The results show that soil respiration was lower in September when compared with measurements done in June and July. The highest values of soil respiration were observed during mid-day and the lowest during evenings and nights. The temperatures of OTC plots were, on average, 1.16 °C higher than control plots, and OTC plots had significantly lower soil water content than control plots. During this research, the soil respiration increased with higher temperature but was not different ...